Comparative study of three zootechnical additives on the production and sanitary behavior of pigs in the post-weaning stage - Flores-Mancheno, Luis Gerardo; García-Hernández, Yaneisy; Usca-Méndez, Julio Enrique; Caicedo-Quinche, William Orlando (Universidad Pedagógica y Tecnológica de Colombia, 2016)
The objective of the study was to compare the effect of three additives (two probiotics and antibiotic) on productive performance and health of pigs in the post-weaning period. For this 120 barrows of the crossing Landrace x Large White with father Belgian White x Petrain were used, they were of 28 days of age and 6.87 kg, divided into three experimental groups based on a completely randomized design and each one with four replications The treatments (T) evaluated were; 1 kg of virginiamycin at 2% per ton of feeding (T1), 1 kg of probiotic with Saccharomyces cerevisiae, Bacillus subtilis and digestive enzymes per ton of feeding (T2) and 15 mL of Ecuadorian preparation with lactic acid bacteria, yeasts and enzymes per kg of body weight (BW) of animals (T3). In this last group it was where the highest final bodyweight was obtained (25.85 kg, P <0.0001) and the best total weight gain (18.97 kg, P <0.0001) and daily (451.75 g /d, P <0.0001). Also, for the same group the conversions of dry matter, crude protein and metabolizable energy were found to be more efficient (1.52 kg/kg of BW; 381.57 g/ kg of PV and 22.99 MJ / kg of BW, respectively). The percentage of animals with diarrhea differed (P <0.0001) between the group that received virginiamycin (50.61%) and microbial additives (27.98% and 21.39%), with no differences between these last two. It is concluded that microbial additives improve the productive and sanitary performance of post -weaning pigs with regards to virginiamycin, and this effect was greater with the Ecuadorian microbial preparation.